2011
DOI: 10.1039/c1pp05065f
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of the antitumoral drugs Doxorubicin and Sabarubicin with telomeric G-quadruplex in basket conformation: ground and excited state properties

Abstract: We studied the binding of two anthracycline drugs, Doxorubicin and Sabarubicin, to a model telomeric sequence 5'-d[GGG(TTAGGG)(3)]-3' (21-mer), assuming the basket G-quadruplex (G4) conformation in Na(+)-rich aqueous solution. We used an approach that combines spectroscopic and microcalorimetric techniques to obtain information about ground and excited state properties of the most stable complexes. Both drugs bind to the 21-mer in basket conformation and complexes of 1:1 and 2:1 drug : 21-mer stoichiometry coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 61 publications
4
34
1
Order By: Relevance
“…CD spectroscopy has shown that DOX molecules bind Tel21 in their monomeric form. Typically, fluorescence titration yields two binding constants, log K 1 =5.6±0.3 and log K 21 =11.2±0.7; these values correspond to the formation of 1:1 and 2:1 DOX–Tel21 complexes, respectively . For comparison, we estimated the binding constant of DOX to d(GC) 10 duplexes by steady‐state absorption spectroscopy, under the same buffer conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CD spectroscopy has shown that DOX molecules bind Tel21 in their monomeric form. Typically, fluorescence titration yields two binding constants, log K 1 =5.6±0.3 and log K 21 =11.2±0.7; these values correspond to the formation of 1:1 and 2:1 DOX–Tel21 complexes, respectively . For comparison, we estimated the binding constant of DOX to d(GC) 10 duplexes by steady‐state absorption spectroscopy, under the same buffer conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study of DOX–Tel21 complexes by steady‐state spectroscopy combined with micro‐calorimetric techniques and molecular mechanics calculations has suggested the existence of two independent binding sites (BSs; see Scheme S1 in the Supporting Information). The first one (BS1), which is found in the two stoichiometries, results from the interaction of DOX with the bottom of the G4 structure; the presence of the diagonal loop precludes direct π–π stacking on the external guanine tetrads . Such an arrangement is expected to be favourable to electron transfer due to the quasi‐parallel orientation of DOX relative to the guanine tetrads.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations